Some Anatomical and Physiological Aspects of Medical Translation: Lexical equivalence, ubiquitous references and universality of subject minimize misunderstanding and maximize transfer of meaning - Fischbach, Henry (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1986)
AbstractMedical translation is the most universal and oldest field of scientific translation because of the homogeneous ubiquity of the human body (the same in Montreal, Mombasa and Manila) and the venerable history of medicine. Its terminology is mostly of Greco-Latin parentage and thus presents fewer lexicographic problems than other fields of scientific translation. A wealth of superb reference tools are readily accessible. The general miscegenation of the sciences and the extensive "lend-lease" among them require the translator to subject the source language to differential diagnosis if his translation therapy is to be successful.